Strategic Improvement of Physical Work Facilities to Enhance Employee Performance at PDAM Tirta Bahari, Tegal City - Mega Yuliana; Adhitya Yoga Prasetya (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2025)
This research explores strategic improvement of physical work facilities as a crucial driver for enhancing employee performance at PDAM Tirta Bahari, Tegal City. In public service institutions, work performance depends not only on human resource quality but also on the adequacy of physical facilities. Properly designed and maintained facilities improve motivation, concentration, and job satisfaction, while inadequate ones create discomfort, stress, and inefficiency. This study adopts a qualitative descriptive approach using literature review, observation, and documentation to examine the relationship between work environment conditions and employee performance. The results reveal that physical facilities directly influence motivation, safety, and overall organizational productivity. Improving ergonomics, cleanliness, and maintenance routines can foster greater work efficiency and reduce absenteeism. Furthermore, physical facilities serve as an expression of the organization’s commitment to employee welfare and professional service delivery. This paper concludes that physical facility management should be integrated strategically within human resource management to ensure sustainable performance improvement.